2014
DOI: 10.1002/jwmg.698
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA to describe and quantify interspecific killing of fishers in California

Abstract: Interspecific killing is common among carnivores and can have population-level effects on imperiled species. The fisher (Pekania [Martes] pennanti) is a rare forest carnivore in western North America and a candidate for listing under the United States Endangered Species Act. Interspecific killing and intraguild predation are poorly understood in fishers and potential threats to existing western populations. We studied the prevalence and patterns of interspecific killing of fishers in the southern Sierra Nevada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…Predation by sympatric, larger carnivores (e.g. bobcats, mountain lions) has been identified as one of the greatest natural sources of mortality for fishers (Gabriel et al., ; Wengert et al., ). Our results suggest that interspecific interactions within the mesopredator guild is a previously unexplored hypothesis that requires attention.…”
Section: Discussionmentioning
confidence: 99%
“…Predation by sympatric, larger carnivores (e.g. bobcats, mountain lions) has been identified as one of the greatest natural sources of mortality for fishers (Gabriel et al., ; Wengert et al., ). Our results suggest that interspecific interactions within the mesopredator guild is a previously unexplored hypothesis that requires attention.…”
Section: Discussionmentioning
confidence: 99%
“…Research on fisher habitat selection has focused on their selection of forest structure at several spatial scales (Raley et al , Lapoint , Sauder and Rachlow ), and especially at the scale of den and rest sites (Zielinski et al , Weir et al , Happe et al ). Previous research has also identified important influences of prey and predators on fisher survival (Wengert et al , Gabriel et al ) and body condition (Kirby et al ). The influence of prey and predators on habitat selection is frequently hypothesized (Raley et al , Sauder and Rachlow , Lewis et al ) but has rarely been tested for fishers (Arthur et al ).…”
mentioning
confidence: 99%
“…Fishers in western North America coexist with a more diverse carnivore community than fishers in the east (Lapoint et al ), and intraguild predation is a major mortality source in California, particularly from bobcats and cougars ( Puma concolor ; Wengert et al , Gabriel et al ). Bobcats and coyotes act as competitors and predators for fishers (Wengert et al ), leading to a possible food‐safety tradeoff for fishers (Bischof et al ), where areas with abundant prey for fishers may also have a high abundance of bobcats and coyotes.…”
mentioning
confidence: 99%
“…Natural mortality from predation, injuries, starvation, or disease will occur in all wildlife populations but may increase because of imbalances in abundance of interacting species from harvest, habitat change associated with resource extraction, and the introduction of non‐native species or pathogens (Goodrich and Buskirk , Roemer et al , Pedersen et al , Clifford et al , Ritchie and Johnson ). Data on baseline levels of natural mortality are seldom available (Wengert et al ), yet additional mortality within a population from human‐linked causes such as roadkill or exposure to rodenticides may alter the growth trajectory of a population, thereby threatening persistence whether or not the number of deaths from natural sources has changed over time (Sweitzer et al , Hayes et al ). For these reasons, quantitative data on the relative importance of natural and human‐linked mortality risks can inform mitigation efforts to prevent local and regional extinction (Newmark , Clevenger et al , Ceballos and Ehrlich ).…”
mentioning
confidence: 99%
“…Known causes of death, which may be limiting numeric and spatial recovery of fisher populations, include exposure to disease and debilitating injury (Aubry and Raley , Larkin et al , Keller et al , Gabriel , Lewis ), predator attacks (Truex et al , Aubry and Raley , Wengert et al ), incidental or targeted fur trapping (Lewis and Zielinski , Koen et al , Lewis ), vehicle strikes (Krohn et al , York , Chow , Lewis , Spencer et al ), entrapment in water tanks or other human structures (Folliard , Truex et al , Davis ), and direct consumption and secondary exposure to rodenticides and insecticides (i.e., toxicants) at trespass marijuana grow sites in public wildlands (Gabriel et al , Thompson et al ). Several reports suggest that fisher survival may vary between sexes or according to season associated with period‐specific life‐history events (e.g., reproduction, breeding movements, dispersal; Powell and Leonard , Lewis , Sweitzer et al ), higher energetic costs during winter (Powell ), or timing of exposure to toxicants (Thompson et al , Gabriel et al ).…”
mentioning
confidence: 99%